PATTERNS AND PROBLEMS OF INTERNATIONAL STUDENTS' SELF-ADJUSTMENT (Case Study of International Students at Universitas Pendidikan Indonesia) - Emehinola, Taiwo Temitayo (2020)
International students are confronted with various challenges while adjusting to their new environment when they go abroad to study, these problems can lead to abnormal adjustments that can affect their psychological well-being. This study aims to explore the self-adjustment of international students (a case study of international students at Universitas Pendidikan Indonesia). A qualitative research approach and a case study method was used for this study. Data was collected from five (5) international students at Universitas Pendidikan Indonesia (UPI) using interview. The research findings shows that at the beginning of studying in UPI especially for the first three (3) months, most international students tend to face excessive emotions and make use of psychological mechanisms. They exhibit rational deliberation and self-direction. Most international students are unable to make use of past experiences and they show unrealistic and subjective attitude which is a clear sign of an abnormal adjustment. International students also face self-adjustment problems such as language barriers, isolation from classmates, cultural differences, unpunctuality, financial problems, and technical problems. These students cope with these adjustment problems by seeking help, improving their language skills, relating with other international students, denial of the problem, entertainment, and prayers. This study also shows that international students from Asia and America exhibited normal adjustments on many normal adjustment indicators. International students from Europe and Africa exhibited normal adjustments on few normal adjustment indicators. The findings of this study creates an urgency for the need of a comprehensive guidance and counseling program tailored towards international students to help them cope with adjustment issues.